(untitled) (Journal of Informatics Education and Research, 2025)
This research paper aims to address a highly sensitive and important issue that has garnered widespread media attention in both the Western and Arab worlds: the phenomenon of overtourism, which has become increasingly prevalent in several European countries such as Venice, Paris, and others. The World Tourism Organization has warned that this phenomenon may expand to affect countries worldwide by 2030. This study focuses on the city of Barcelona, Spain, where the issue has recently resurged strongly in the aftermath of the COVID-19 crisis. This resurgence is seen as a global retaliatory reaction to the lockdown measures, airport and port closures, and enforced social distancing implemented to overcome the pandemic. These developments have prompted the Catalonian city of Barcelona to consider adopting responsible tourism as a model and strategic solution to mitigate the negative impacts caused by overtourism on this unique tourist destination with its timeless landmarks.